Stability and Tracking Control of Nonlinear Rigid-Body Ship Motions - Chatchawan Aumtab (2022)
The stability and tracking controls of a dynamic ship system are studied in this paper, in order to stabilize and track the desired path of a catamaran ship system. The ship sails on a river that is prone to currents, wind, and unknown disturbances from the surrounding environment. Hence, the ship system potentially has stability problems. This paper presents a method for controlling the trajectory of a nonlinear ship system and controlling the ship stabilization. Three steps of the fundamental equations of constrained motion (FECM) with an uncertainty control are used to examine a control force to stabilize and track the ship system. The ship system is considered with six degrees of freedom to describe the stabilization of the ship’s rigid-body motion. The results show the efficiency of the control forces from the FECM, with an uncertainty controller applied to the ship system. They guarantee that the conditions of the ship system are satisfactory, and that the ship follows the desired path.